TRANSITION TO A GREEN ECONOMY IS A FACTOR OF SOCIO-ECONOMIC DEVELOPMENT (Conferencea, 2024)
The article discusses the primary causes of the emergence of the “green” economy. Analysis was done on the goals and objectives of the growing green economy. It was determined how important it was to implement an economic reform on a national and international scale. We examined the global green economy’s growth rate as well as its degree of development in the most developed nations. It was investigated how institutional and investment determinants affected the greening of the economy. The authors assessed how scientific and technological research affected the economy’s shift to a new paradigm.